Optimasi Quercetin Kombinasi Avobenzone dalam Sediaan Spray Lotion Tabir Surya - Budipratiwi Wisudyaningsih; Elok Rimadani; Lidya Ameliana; Lusia Oktora Ruma Kumala Sari; Yudi Wicaksono; Kuni Zu’aimah Barikah (Universitas Wahid Hasyim Semarang, 2024)
Excessive exposure to ultraviolet radiation can cause various skin problems. This problem can be prevented by using cosmetic products that contain sunscreen ingredients. In this study, optimization of the combination of quercetin and avobenzone in sunscreen spray lotion was carried out using the factorial design method. The aim of this study was to determine the optimum concentrations of avobenzone and quercetin which could provide optimum physicochemical properties and effectiveness of in vitro sunscreen spray lotion. The formula is made with a low concentration of 0.5% quercetin and an upper limit of 3%, while avobenzone has a low level of 2% and an upper level of 4%. Based on the research that has been done, the optimum formula prediction is obtained with a concentration of 0.934% quercetin and 4% avobenzone. The optimum formula has a desirability value of 0.958 and shows the predicted value of software to have an SPF in vitro value of 33.311, a %TE 0.058%, a %TP 0.002%, a viscosity of 10 dPa.s, and a pH of 5.689. The results of the analysis using the t-test (one sample t-test) with a 95% level of confidence between the software prediction results and the observation results showed a value of > 0.05, which means that there was no significant difference between the software prediction results and the observation group.